Relationship between Demographic Characteristics and Moral Sensitivity among Professional Nursing Students in Bali - Ni Putu Emy Darma Yanti; Komang Menik Sri Krisnawati (Jurnal Ners, 2020)
Introduction: Moral sensitivity is indispensably required in nurses for them to be aware of and be able to understand clients’ needs. This study aimed to determine the relationship between demographic characteristics and moral sensitivity among professional nursing students in Bali.Methods: The research used a descriptive-correlation method and a cross-sectional approach. The study population was all professional nursing students in Bali with 162 students as research respondents, sampled using the purposive sampling technique. The dependent variable is the moral sensitivity among professional nursing students and the independent variable is the demographic characteristics consisting of gender, age, religion, and number of siblings. Data were collected by means of a moral sensitivity questionnaire for nursing students developed by Lutzen in 1993 consisting of 27 statements.Results: The results of this study show that there is a significant relationship between religion and moral sensitivity (p=0.027; α=0.05), and that there is no relationship between sex, age, and number of siblings and moral sensitivity (p>0.05; α=0.05).Conclusion: The nursing students’ level of faith and understanding of their respective religious teachings can increase their moral sensitivity in providing nursing care.